2014
DOI: 10.1007/s00787-013-0499-2
|View full text |Cite
|
Sign up to set email alerts
|

Reducing child conduct disordered behaviour and improving parent mental health in disadvantaged families: a 12-month follow-up and cost analysis of a parenting intervention

Abstract: The effectiveness of the Incredible Years Basic parent programme (IYBP) in reducing child conduct problems and improving parent competencies and mental health was examined in a 12-month follow-up. Pre- to post-intervention service use and related costs were also analysed. A total of 103 families and their children (aged 32-88 months), who previously participated in a randomised controlled trial of the IYBP, took part in a 12-month follow-up assessment. Child and parent behaviour and well-being were measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Two studies of IY with longer-term follow-ups found that improvements in ECBI-I score were sustained and accompanied by decreased costs of health and social services or a reduction in the likelihood that formal services were used. 172,173 The US-based evaluation of the multifaceted Perry Preschool Program suggests a possible long-term impact on conduct disorder, criminal behaviour and employment. 174 Evidence from model-based analyses suggests that parenting programmes are likely to provide substantial savings (e.g.…”
Section: Results and Discussion Of Wider Health Benefits And Possiblementioning
confidence: 99%
“…Two studies of IY with longer-term follow-ups found that improvements in ECBI-I score were sustained and accompanied by decreased costs of health and social services or a reduction in the likelihood that formal services were used. 172,173 The US-based evaluation of the multifaceted Perry Preschool Program suggests a possible long-term impact on conduct disorder, criminal behaviour and employment. 174 Evidence from model-based analyses suggests that parenting programmes are likely to provide substantial savings (e.g.…”
Section: Results and Discussion Of Wider Health Benefits And Possiblementioning
confidence: 99%
“…Five of the seven RCTs contained a cost‐effectiveness evaluation (Muntz et al ; Atherton ; Barlow et al ; Edwards et al ; McIntosh et al ; O'Neill et al ; Simkiss et al ). Of the two remaining RCTs, one (Charles et al ) reported the cost of the intervention, and the other (McGilloway et al ) reported the cost of service use.…”
Section: Resultsmentioning
confidence: 99%
“…The studies took place predominantly in deprived areas of Wales (four studies) (Muntz et al ; Atherton ; Edwards et al ; Charles et al ; Simkiss et al ). Two were conducted in England (Barlow et al ; McIntosh et al ; Bonin et al ) and two each in Ireland (McGilloway et al ; O'Neill et al ) and the USA (Reynolds & Temple ; Reynolds et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Parenting programmes have achieved broad support as preventative interventions that may positively affect childhood well‐being. However, current intervention packages with a substantial evidence base such as Incredible Years and the Triple P Programme tend to focus on parental management of children's behaviour or are primarily targeted at families with children of 2 years and over. Attachment relationships and parental sensitivity – key psychological mechanisms for the transmission of resilience – are not the primary focus of these programmes .…”
mentioning
confidence: 99%